An Analysis of the Progression of Conjunctivalisation after Transplantation of Cultivated Corneal Epithelium - Dariusz Dobrowolski; Boguslawa Orzechowska-Wylegala; Bogumil Wowra; Ewa Wróblewska-Czajka; Maria Grolik; Edward Wylegala (Journal of Ophthalmology)
Purpose. To analyse the recurrence of superficial neovascularisation after previous corneal surface reconstruction with cultivated corneal epithelial cells. Materials and Methods. Forty-eight eyes underwent autologous transplantation of cultivated corneal epithelium to treat partial or total limbal stem cell deficiency caused by chemical or thermal injury. The carrier for the epithelial sheets was a denuded amniotic membrane. Follow-up was conducted for up to 120 months. Recurrent revascularisation (measured in terms of clock hours affected) was evaluated with slit-lamp examination and the support of confocal microscopy. Results. During the long-term observation, only 7 eyes had stable epithelia with no neovascularisation from the conjunctiva. Nineteen eyes developed pathologic vessels in 1 quadrant, with additional 4 eyes developing them in 2 quadrants. Twelve patients developed subtotal or total conjunctivalisation of the corneal surface. They were referred for second cultivated epithelium transplantation (3 patients), allogenic keratolimbal transplantation (7 patients), or keratoprosthesis (2 patients). Six patients withdrew consent. The use of confocal scans of up to 100 µm in resolution enabled the detection of pathologic microvasculature originating from the conjunctiva and the exclusion of stromal vascular ingrowth. Conclusions. Local ingrowth of the conjunctiva is a common complication after the transplantation of cultivated epithelial cells. Severe and progressive vascularisation inevitably leads to graft failure. However, if local ingrowth stops before reaching the central cornea, the treatment even with this complication can be considered a success.